(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The role and procedures for accountability in the spending units significant impact in enhancing the results of the budget it is found by studying and comparing the results of the implementation of the budget for the research sample for a period of two years to repeat the same deviations and irregularities of Guanyin, regulations and instructions that have occurred in implementation results and two consecutive Kaltjaoz customizations and low rates of implementation and the lack of exchange of allocations Finance despite the presence budget note that such remarks are always indicate in regulatory reports, but these observations repeated Bostmr in the results of the implementation of the budget. Which clearly reflects the absence of the role of accountability and completely with respect to the budget and allocations and the results of its implementation, while focused accountability focus on the provision of funds resulting from the waste and extravagance in public money as a result of tarry some sample Kmstraeat and costs of speculative activities and what has been retrieved from the payments to the Treasury. The main conclusions reached by the research is limited accountability and follow-up on the waste and extravagance in public money on procurement and other aspects by the authorities that the follow-up and accountability and the lack of accountability on the results of implementation of the budget, which led to obtain deviations in the implementation results and repeat the same distractions and observations in the following years and the most important recommendations need for the views of accountability and follow-up to hold accountability for the results of the implementation of the budget and the lack of focus or restricted to aspects of waste and extravagance in the money for procurement and to be an internal control and primary actor Aldror follow-up and audit the implementation of the budget, monthly or quarterly, and make sure not to encroach upon the budget allocations by the instructions of the implementation of commitments the budget and all instructions issued in this regard. المقدمة